Sistem Kendali PID Untuk Intensitas Cahaya Ruang Berbasis Labview - Diki Muhamad Sobirin (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - This tool is made to facilitate human work in controlling the intensity of light on the lamp using PID control. To adjust the light in a room requires a control of light intensity which will adjust the light intensity and conditions in the room. So one method is to use PID control using a light sensor. The intensity control system emitted by lights with a light sensor will adjust to the conditions of the room. With the addition of PID control on the light sensor so that it can speed up the response of the system. To design the light intensity control, this study was conducted. Where the value of set (set point) as a value that will be a reference of the control system commonly called Set Value (SV). Then the controller that will become the control system is the PID control system. Then go to the MOSFET driver to convert it from the microcontroller block to the actuator. After that, proceed to the plant system section where there is an actuator in the form of a DC light and its light intensity is measured with an LDR that functions as feedback in the form of a digital light sensor. The digital signal from the sensor output will then be entered into the controller PV). Interference will be given to the actuator in the form of external light such as incoming sunlight, or, can be the addition of light and / or reduction of light with lights. Keyword : Keyword : PID, Light Intensity, Light Sensors